PENGARUH INTELLECTUAL CAPITAL, AUDITOR SWITCHING, DAN WHISTLEBLOWING SYSTEM TERHADAP INTEGRITAS LAPORAN KEUANGAN - Amanda Uke Febrianti, (2023)
This study aims to determine the effect of intellectual capital, auditor switching, and the whistleblowing system on the integrity of financial reports in infrastructure sector companies listed on the IDX for the 2019-2021 period. The research conducted is a type of quantitative research using secondary data in the form of data from annual reports and audited financial reports. The sample used in this study amounted to 50 companies with a purposive sampling technique. The technique used to analyze the data in this study is the regression model selection test, classical assumption test, hypothesis testing, and multiple linear regression. Based on the results of the data analysis that has been presented it can be concluded that 1) intellectual capital has no influence on the integrity of financial statements; 2) auditor switching has a positive influence on the integrity of financial statements; 3) the whistleblowing system has no effect on the integrity of financial statements. Keywords: intellectual capital, auditor switching, and whistleblowing system